2014
DOI: 10.1186/1756-0500-7-664
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of pomegranate juice reduces acute lung injury secondary to hyperoxia in an animal model

Abstract: BackgroundHyperoxia triggers the release of toxic reactive oxygen species (ROS). Pomegranate Juice (PJ) is a rich source of potent antioxidants. We assessed the effects of PJ supplementation on Acute Lung Injury (ALI) in adult rats exposed to hyperoxia for 5 days.MethodsAdult rats were divided into four different groups: control, hyperoxia, hyperoxia + PJ and PJ. Animals were placed in chambers containing either room air or oxygen above 95% for a total of 5 days. Two different PJ concentrations were utilized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Some therapeutic approaches include improvement of memory (Ropacki et al, 2013;Bookheimer et al, 2013), neurodegenerative disorders (Forouzanfar et al, 2013), anti-diabetic effects (Middha et al, 2013;Raafat and Samy, 2014), hepatoprotective effects (Middha et al, 2013), anti-bacterial effects (Howell and Souza, 2013), anti-viral effects (Howell and Souza, 2013), antiinflammatory effects (Colombo et al, 2013), cardiovascular disorders (Aviram and Rosenblat, 2012) and cancer treatment (Bhatia et al, 2013;Vlachojannis et al, 2015). A prominent health benefit acquired by pomegranate is its capacity to oppose oxidative stress and attenuate number of inflammatory mediators (Costantini et al, 2014;Husari et al, 2014;Shukla et al, 2008). It is of great importance to maintain appropriate physiologic condition by balancing free radicals and antioxidants for prevention and treatment of chronic diseases like atherosclerosis, cancer, diabetes, arthritis, aging etc.…”
Section: Pomegranatementioning
confidence: 99%
“…Some therapeutic approaches include improvement of memory (Ropacki et al, 2013;Bookheimer et al, 2013), neurodegenerative disorders (Forouzanfar et al, 2013), anti-diabetic effects (Middha et al, 2013;Raafat and Samy, 2014), hepatoprotective effects (Middha et al, 2013), anti-bacterial effects (Howell and Souza, 2013), anti-viral effects (Howell and Souza, 2013), antiinflammatory effects (Colombo et al, 2013), cardiovascular disorders (Aviram and Rosenblat, 2012) and cancer treatment (Bhatia et al, 2013;Vlachojannis et al, 2015). A prominent health benefit acquired by pomegranate is its capacity to oppose oxidative stress and attenuate number of inflammatory mediators (Costantini et al, 2014;Husari et al, 2014;Shukla et al, 2008). It is of great importance to maintain appropriate physiologic condition by balancing free radicals and antioxidants for prevention and treatment of chronic diseases like atherosclerosis, cancer, diabetes, arthritis, aging etc.…”
Section: Pomegranatementioning
confidence: 99%
“…Furthermore, in this study, we have shown that cigarette smoke exposure is also associated with significant surge in the expression of inflammatory mediators (TNF-α, IL-1β) expressed in the aortic tissues coupled with an up-regulation of Bdkrb1 (Figures 4, 5). We have shown previously an elevation in the inflammatory pathways in lungs of CS group (Husari et al, 2014). …”
Section: Discussionmentioning
confidence: 72%
“…In our model, the “nose only” delivery paradigm, which mimics primary smoking exposure, delivered cigarette smoke directly into the airways of tested animals and eliminated inadequate cigarette smoke exposure secondary to whole-body exposure. Our smoke exposure model was previously employed to assess different pulmonary events post smoke exposure (Raza et al, 2013; Husari et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS may be produced by inflammatory cells (macrophages and neutrophils) trying to fight infections, or by dysfunctional mitochondria or enzymatic systems in alveolar epithelial cells and capillary endothelial cells after lung tissue damage by hyperoxia, electrophilic xenobiotics, and shear stress (Brune et al 2013; Warabi et al 2007; Bernard et al 2014; Reddy et al 2009c). Antioxidants have been shown to reduce the severity of ALI/ARDS in multiple mouse models that use different initiating insults, highlighting the central role of ROS in the pathophysiology of ALI/ARDS (Aggarwal et al 2012; Howard et al 2014; Ye et al 2015; Husari et al 2014; Shohrati et al 2014; Zhao et al 2014; Lingaraju et al 2015; Hu et al 2015; Yilmaz et al 2014; Yamamoto et al 2012; Campos et al 2012). …”
Section: Current Therapeutic and Treatment Options For Ali/ardsmentioning
confidence: 99%